High-fluidity low-temperature-resistant super-tough nylon composite material and preparation method thereof
By introducing dynamic covalent bonds and metal coordination ions into the toughening agent of nylon composites, and using PA composites with different structures, the problem of poor impact performance of existing nylon composites in low temperature and dry states is solved. A nylon composite material with high flowability, easy processing and excellent low temperature resistance.
Patent Information
- Application Number
- CN202411627110.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nylon composite materials have poor impact performance at low temperature and dry states, and the chemical permanent cross-linking of tougheners leads to a decrease in fluidity and difficult processing.
By introducing dynamic covalent bonds and metal coordination ions into the elastomer toughening agent, the chemical permanent crosslinking degree is reduced, the compatibility of the toughening agent and nylon is improved, and the interpenetrating network is formed by using PA composites of different structures. structure.
It has achieved high flow and easy-to-process nylon composite materials, and has excellent low temperature and impact resistance, and is suitable for high-speed rail, automobile and other fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, and in particular to a high-fluidity, low-temperature-resistant and ultra-tough nylon composite material and a preparation method thereof. Background Art
[0002] Nylon (PA) has excellent comprehensive properties such as high strength, heat resistance, creep resistance, wear resistance, oil resistance and chemical corrosion resistance, and is widely used in high-speed rail, automobiles, electronic and electrical, mechanical equipment and other fields. However, PA materials, especially resins such as PA6, PA46, PA56, and PA66, have disadvantages such as poor low-temperature and dry impact properties, low notched impact strength, and high water absorption, which limits its application.
[0003] Adding elastomer toughening agent is the most commonly used modification method to toughen PA, which can significantly improve the impact strength of PA at low temperature and in dry state. At present, conventional toughening agents are modified by directly grafting active groups such as maleic anhydride (MAH), itaconic acid (ITA), and glycidyl methacrylate (GMA) on elastomers under the action of initiators. However, this method will cause serious cross-linking of the grafted products, and the stable chemical connection formed by the reaction between the grafted groups and the amino or carboxyl groups in PA will easily form micro-crosslinks between molecules. These factors will greatly reduce the fluidity of the blends in the application of super-tough PA materials, and ultimately lead to difficulties in processing the modified materials, the inability to increase production, and the difficulty in dispersing the color powder in dyed products. Chinese patent CN116102881B discloses a high-fluidity nylon toughening agent and its preparation method. The invention is prepared from the following raw materials in parts by weight: 20-90 parts of propylene-based elastomer, 10-80 parts of vinyl elastomer, 0.3-5 parts of the first grafting monomer, 0.1-5 parts of the second grafting monomer, 0.01-0.5 parts of the initiator, and 0.1-2 parts of the diluent. The invention combines two elastomers and two grafting monomers to increase the fluidity of the toughening agent while ensuring the toughening effect. However, this method still cannot fundamentally improve the chemical permanent cross-linking of the toughening agent, and the improvement in fluidity is not significant enough. In addition, it is difficult to achieve the requirement of ultra-high toughness by simply melt-mixing the toughening agent with PA. This requires the development of a new modification technology, starting from the toughening agent molecular chain structure and the composite material system at the same time, while ensuring that the PA composite material system has high fluidity and easy processing in the molten state, and its room temperature and low temperature glass state has the characteristics of high toughness to meet the development needs of products in related fields. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a high-fluidity, low-temperature-resistant, ultra-tough nylon composite material and a preparation method thereof. By introducing dynamic covalent bonds and metal coordination ions into an elastomer toughening agent, the method not only reduces the degree of chemical permanent crosslinking in the elastomer toughening agent, but also improves the compatibility between the elastomer toughening agent and PA, and also reduces the effect of stable chemical bonds on the decrease in fluidity of the blend. The toughening agent is introduced into a PA composite matrix with different structures, so that the composite material can maintain good fluidity and have excellent toughness and low-temperature resistance.
[0005] The present invention is realized by the following technical scheme: A high-fluidity, low-temperature-resistant, ultra-tough nylon composite material comprises the following components, measured in parts by weight:
[0006] 23-64 parts of monomer homopolymer nylon;
[0007] 28-54 parts of multi-molecular monomer copolymerized nylon;
[0008] 7-22 parts of dynamic cross-linking toughening agent;
[0009] 0.2-0.8 parts of antioxidant;
[0010] 0.2-0.8 parts of lubricant;
[0011] The dynamic cross-linking toughening agent comprises ethylene octene copolymer, ethylene propylene diene monomer rubber, maleic anhydride powder, a compound containing a dynamic covalent bond, a lubricant and an antioxidant, and is formed by treating an initiator and a weakly alkaline metal hydroxide. The method for preparing the dynamic cross-linking toughening agent comprises the following steps:
[0012] a) uniformly mixing ethylene octene copolymer, EPDM rubber, maleic anhydride powder, a compound containing a dynamic covalent bond, a lubricant and an antioxidant to obtain a primary mixture;
[0013] b) feeding the primary mixture into a twin-screw extruder, feeding a saturated solution of an initiator in ethanol at room temperature through a liquid metering pump at a first side feeding port, and feeding a weakly alkaline metal hydroxide through a second side feeding port;
[0014] c) extruding and granulating at a temperature of 70-200° C. to obtain the dynamic crosslinking toughening agent.
[0015] As a preferred technical solution, the monomer homopolymer nylon is at least one of PA6, PA11 or PA12, and the multi-molecular monomer copolymer nylon is at least one of PA66, PA66 / 6 copolymer, PA56, PA46, PA610, PA612, PA1010, PA1012 or PA1212.
[0016] As a preferred technical solution, the components of the dynamic cross-linking toughener include 35-64 parts of ethylene octene copolymer (POE), 35-61 parts of ethylene propylene diene monomer rubber (EPDM), 0.5-2.9 parts of maleic anhydride powder, 0.1-0.3 parts of dynamic covalent bond-containing compounds, 0.2-0.4 parts of lubricants and 0.2-0.4 parts of antioxidants.
[0017] As a preferred technical solution, the initiator is one of diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxide hexane (DBPH), dibenzoyl peroxide or diisopropylbenzene di-tert-butylperoxide, and the weakly alkaline metal hydroxide is at least one of aluminum hydroxide, copper hydroxide, zinc hydroxide, magnesium hydroxide, nickel hydroxide or manganese hydroxide.
[0018] As a preferred technical solution, the dynamic covalent bond-containing compound is prepared by chemical reaction of at least one of 1-mercaptoglycerol, α-allyl glyceryl ether and phenyl-1,4-diboric acid, and the reaction product is at least one of double-terminated vinyl borate, double-terminated mercapto borate or mercapto vinyl borate.
[0019] As a preferred technical solution, the antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1098, antioxidant 245, antioxidant 1076, antioxidant AO-30, antioxidant 3391, antioxidant 445, antioxidant H3336, antioxidant PolyAd HS-02, antioxidant s9228, antioxidant 168, antioxidant 626 or antioxidant PEPQ.
[0020] As a preferred technical solution, the lubricant is at least one of calcium stearate, OP wax, E wax, rice bran wax, silicone powder, ethylene bisstearamide or pentaerythritol stearate.
[0021] As a preferred technical solution, when preparing the dynamic cross-linking toughening agent, the feeding amount of the main feed of the screw extruder is 99-100 parts by weight, the injection amount of the liquid metering pump at the first side feeding port is 0.2-0.6 parts, and the feeding amount measured by the metering scale at the second side feeding port is 0.4-0.8 parts.
[0022] As a preferred technical solution, when the dynamic cross-linking toughening agent is prepared, the temperatures of extruder zones 1 to 12 are set to 70±10°C, 170±10°C, 180±10°C, 190±10°C, 200±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, and the head temperature is 200±10°C.
[0023] The method for preparing the high-fluidity, low-temperature-resistant and ultra-tough nylon composite material of the present invention comprises the following steps:
[0024] a) drying the nylon resin;
[0025] b) putting the monomer homopolymer nylon, multi-molecular monomer copolymer nylon, dynamic cross-linking toughening agent, antioxidant and lubricant into a mixer according to the required weight proportions and mixing them evenly;
[0026] c) adding the mixture into a twin-screw extruder for melt blending, and extruding and granulating to obtain the high-fluidity, low-temperature-resistant and ultra-tough nylon composite material.
[0027] The beneficial effects of the present invention are:
[0028] (1) The introduction of compounds containing dynamic covalent bonds can form dynamic cross-linking bonds in the toughening agent system, which can effectively reduce the degree of chemical permanent cross-linking in the toughening agent system. At the same time, dynamic reversible conversion of borate chemical cross-linking bonds can occur at high temperatures, which has little effect on the processability of the system and enables the PA composite material to maintain good toughness and strength at room temperature and low temperature after molding.
[0029] (2) Metal coordination ions are simultaneously introduced into the elastomer toughening agent. This method can produce a synergistic effect with the dynamic chemical bonds to reduce the chemical permanent crosslinking produced during the preparation and processing of the elastomer toughening agent. It can also improve the compatibility between the toughening agent and PA and limit the crystallinity of the molecular chain of PA. It has little effect on the fluidity and processability of the PA composite melt. During the molding process of the composite material, the metal coordination ions can induce the composite material system to form physical crosslinks, so that the PA material has ultra-high impact toughness and good tensile strength.
[0030] (3) The compounding of PA with different molecular structures as the matrix can form an interpenetrating network structure between molecules, which can restrict the crystallinity between molecules to a certain extent, improve the impact resistance of the composite material system, and have good fluidity and processability.
[0031] (4) The PA composite material of the present invention has the characteristics of high fluidity, easy processing, low temperature resistance, excellent impact resistance, etc., and has wide application value in high-speed rail, automobiles, sporting goods and cold storage equipment parts. DETAILED DESCRIPTION
[0032] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.
[0033] Any feature disclosed in this specification (including any additional claims and abstract), unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.
[0034] The high-fluidity, low-temperature-resistant and ultra-tough nylon composite material of the present invention comprises the following components, measured in parts by weight:
[0035] 23-64 parts of monomer homopolymer nylon;
[0036] 28-54 parts of multi-molecular monomer copolymerized nylon;
[0037] 7-22 parts of dynamic cross-linking toughening agent;
[0038] 0.2-0.8 parts of antioxidant;
[0039] 0.2-0.8 parts of lubricant;
[0040] The dynamic cross-linking toughening agent comprises ethylene octene copolymer, ethylene propylene diene monomer rubber, maleic anhydride powder, a compound containing a dynamic covalent bond, a lubricant and an antioxidant, and is formed by treating an initiator and a weakly alkaline metal hydroxide. The method for preparing the dynamic cross-linking toughening agent comprises the following steps:
[0041] a) uniformly mixing ethylene octene copolymer, EPDM rubber, maleic anhydride powder, a compound containing a dynamic covalent bond, a lubricant and an antioxidant to obtain a primary mixture;
[0042] b) feeding the primary mixture into a twin-screw extruder, feeding a saturated solution of an initiator in ethanol at room temperature through a liquid metering pump at a first side feeding port, and feeding a weakly alkaline metal hydroxide through a second side feeding port;
[0043] c) extruding and granulating at a temperature of 70-200° C. to obtain the dynamic crosslinking toughening agent.
[0044] Among them, the monomer homopolymer nylon is at least one of PA6, PA11 or PA12, and the multi-molecular monomer copolymer nylon is at least one of PA66, PA66 / 6 copolymer, PA56, PA46, PA610, PA612, PA1010, PA1012 or PA1212.
[0045] The components of the dynamic cross-linking toughening agent include 35-64 parts of ethylene octene copolymer (POE), 35-61 parts of ethylene propylene diene monomer rubber (EPDM), 0.5-2.9 parts of maleic anhydride powder, 0.1-0.3 parts of a compound containing a dynamic covalent bond, 0.2-0.4 parts of a lubricant and 0.2-0.4 parts of an antioxidant.
[0046] Among them, the initiator is one of diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxide hexane (DBPH), dibenzoyl peroxide or diisopropylbenzene di-tert-butylperoxide, and the weakly alkaline metal hydroxide is at least one of aluminum hydroxide, copper hydroxide, zinc hydroxide, magnesium hydroxide, nickel hydroxide or manganese hydroxide.
[0047] The dynamic covalent bond-containing compound is prepared by chemical reaction of at least one of 1-mercaptoglycerol, α-allyl glyceryl ether and phenyl-1,4-diboric acid, and the reaction product is at least one of double-terminated vinyl borate, double-terminated mercapto borate or mercapto vinyl borate.
[0048] The antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1098, antioxidant 245, antioxidant 1076, antioxidant AO-30, antioxidant 3391, antioxidant 445, antioxidant H3336, antioxidant PolyAd HS-02, antioxidant s9228, antioxidant 168, antioxidant 626 or antioxidant PEPQ.
[0049] Wherein, the lubricant is at least one of calcium stearate, OP wax, E wax, rice bran wax, silicone powder, ethylene bisstearamide or pentaerythritol stearate.
[0050] When the dynamic cross-linking toughening agent is prepared, the feeding amount of the main feed of the screw extruder is 99-100 parts by weight, the injection amount of the liquid metering pump at the first side feeding port is 0.2-0.6 parts, and the feeding amount measured by the second side feeding port is 0.4-0.8 parts.
[0051] Wherein, when the dynamic cross-linking toughening agent is prepared, the temperatures of extruder zones 1 to 12 are set to 70±10°C, 170±10°C, 180±10°C, 190±10°C, 200±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, and the head temperature is 200±10°C.
[0052] In order to explain the technical content, purpose and effect of the present invention in detail, the following is explained in conjunction with specific embodiments. In order to ensure the comparability of melt index, the following examples and comparative examples all use PA resin with a relative viscosity of 2.7 as the matrix.
[0053] Example 1
[0054] Preparation of dynamic cross-linking toughening agent: Take 49.5 parts by weight of POE, 48 parts by weight of EPDM, 1.7 parts by weight of maleic anhydride powder, 0.2 parts by weight of double-end vinyl borate, 0.3 parts by weight of ethylene bisstearamide and 0.3 parts by weight of antioxidant (the ratio of 1010 to 168 is 2:1), put them into a mixer and stir until they are evenly mixed to form a primary mixture. The primary mixture is put into the main feed metering hopper of the twin-screw extruder, and the feeding ratio is set to 99 parts by weight. At the first side feed port, 0.4 parts by weight of di-tert-butyl peroxide diisopropylbenzene (BIPB) of a saturated solution of ethanol at room temperature is injected through a liquid metering pump; at the second side feed port, 0.6 parts by weight of aluminum hydroxide is fed through a micro-metering scale. The temperature range of the screw extruder is set to 70-200°C, and the required dynamic cross-linking toughening agent is obtained by extrusion granulation and drying.
[0055] Preparation of super-tough PA composite material: PA resin is dried in advance. 42 parts of PA6, 41 parts of PA66, 16 parts of dynamic cross-linking toughening agent, 0.5 parts of antioxidant (the ratio of 1098 to s9228 is 3:2), and 0.5 parts of OP wax are added to a mixer by weight and mixed evenly, and then the mixture is added to a twin-screw extruder, blended in a molten state, and extruded into granules to finally obtain a high-flowability, low-temperature-resistant, super-tough PA composite material.
[0056] Example 2
[0057] Preparation of dynamic cross-linking toughening agent: Take 64 parts by weight of POE, 35 parts by weight of EPDM, 0.5 parts by weight of maleic anhydride powder, 0.1 parts by weight of double-end vinyl borate, 0.2 parts by weight of ethylene bisstearamide and 0.2 parts by weight of antioxidant (the ratio of 1010 to 168 is 2:1), mix them evenly to form a primary mixture, and then put it into the main feed metering scale of the twin-screw extruder, with a feeding ratio of 99 parts by weight. At the first side feed port, 0.2 parts by weight of BIPB saturated solution at room temperature ethanol is injected through a liquid metering pump; at the second side feed port, 0.8 parts by weight of aluminum hydroxide is fed through a micro-metering scale. The temperature of the screw extruder is set to 70-200°C, and the required dynamic cross-linking toughening agent is obtained by extrusion granulation and drying.
[0058] Preparation of super-tough PA composite material: PA resin is pre-treated by drying. 42 parts of PA6, 41 parts of PA66, 16 parts of dynamic cross-linking toughening agent, 0.5 parts of antioxidant (the ratio of 1098 to s9228 is 3:2), and 0.5 parts of OP wax are mixed evenly by weight, added into a twin-screw extruder, and extruded and granulated after melt blending to obtain a high-flowability, low-temperature-resistant, super-tough PA composite material.
[0059] Example 3
[0060] Preparation of dynamic cross-linking toughening agent: Take 35 parts by weight of POE, 61 parts by weight of EPDM, 2.9 parts by weight of maleic anhydride powder, 0.3 parts by weight of double-end vinyl borate, 0.4 parts by weight of ethylene bisstearamide and 0.4 parts by weight of antioxidant (the ratio of 1010 to 168 is 2:1), mix them evenly to form a primary mixture, and put them into the main feed metering scale of the twin-screw extruder, and the feeding ratio is set to 100 parts by weight. 0.2 parts by weight of BIPB saturated solution of ethanol at room temperature is injected into the first side feed port, and 0.8 parts by weight of aluminum hydroxide is fed into the second side feed port. The extrusion temperature range is 70-200°C, and the required dynamic cross-linking toughening agent is obtained after extrusion granulation and drying.
[0061] Preparation of super-tough PA composite material: After the PA resin is dried, 42 parts of PA6, 41 parts of PA66, 16 parts of dynamic cross-linking toughening agent, 0.5 parts of antioxidant (the ratio of 1098 to s9228 is 3:2), and 0.5 parts of OP wax are evenly mixed by weight, put into a twin-screw extruder for melt blending and extrusion granulation to obtain a high-flowability, low-temperature-resistant, super-tough PA composite material.
[0062] Example 4
[0063] Preparation of dynamic cross-linking toughening agent: 49.5 parts by weight of POE, 48 parts by weight of EPDM, 1.7 parts by weight of maleic anhydride powder, 0.2 parts by weight of double-end vinyl borate, 0.3 parts by weight of ethylene bis stearamide and 0.3 parts by weight of antioxidant (the ratio of 1010 to 168 is 2:1), uniformly mix to obtain a primary mixture, add it to the main feed metering scale of the twin-screw extruder, the feeding ratio is 99 parts by weight, inject 0.4 parts by weight of BIPB saturated solution of ethanol at room temperature into the first side feed port, and feed 0.6 parts by weight of aluminum hydroxide into the second side feed port. The extrusion temperature range is 70-200°C to obtain a dynamic cross-linking toughening agent.
[0064] Preparation of super-tough PA composite material: 23 parts by weight of PA6, 54 parts by weight of PA66, 22 parts by weight of dynamic cross-linking toughening agent, 0.8 parts by weight of antioxidant (the ratio of 1098 to s9228 is 3:2), and 0.2 parts by weight of OP wax are mixed, put into a twin-screw extruder for melt blending and extrusion granulation to obtain a high-flowability, low-temperature-resistant, super-tough PA composite material.
[0065] Example 5
[0066] Preparation of dynamic cross-linking toughening agent: 49.5 parts by weight of POE, 48 parts by weight of EPDM, 1.7 parts by weight of maleic anhydride powder, 0.2 parts by weight of double-end vinyl borate, 0.3 parts by weight of ethylene bisstearamide and 0.3 parts by weight of antioxidant (the ratio of 1010 to 168 is 2:1), uniformly mixed to form a primary mixture, which is fed into the main feed metering scale of the twin-screw extruder, the feed ratio is set to 99 parts by weight, 0.4 parts by weight of BIPB saturated solution of ethanol at room temperature is injected into the first side feed port, and 0.6 parts by weight of aluminum hydroxide is fed into the second side feed port. The extrusion temperature range is 70-200°C to obtain a dynamic cross-linking toughening agent.
[0067] Preparation of super-tough PA composite material: 64 parts by weight of PA6, 28 parts by weight of PA66, 7 parts by weight of dynamic cross-linking toughening agent, 0.2 parts by weight of antioxidant (the ratio of 1098 to s9228 is 3:2), and 0.8 parts by weight of OP wax are mixed evenly, added into a twin-screw extruder for melt blending and extrusion granulation to obtain the desired high-flowability, low-temperature-resistant, super-tough PA composite material.
[0068] Example 6
[0069] Preparation of dynamic cross-linking toughening agent: 49.5 parts by weight of POE, 48 parts by weight of EPDM, 1.7 parts by weight of maleic anhydride powder, 0.2 parts by weight of double-terminal mercapto borate, 0.3 parts by weight of pentaerythritol stearate and 0.3 parts by weight of antioxidant (the ratio of 1010 to 626 is 2:1) are mixed evenly to obtain a primary mixture, and the mixture is fed into the main feed metering scale of a twin-screw extruder, the feeding ratio is 99 parts by weight, 0.4 parts by weight of DCP saturated solution at room temperature ethanol is injected into the first side feed port, and 0.6 parts by weight of magnesium hydroxide is fed into the second side feed port. The screw extrusion temperature is controlled at 70-200°C to obtain the required dynamic cross-linking toughening agent.
[0070] Preparation of super-tough PA composite material: 42 parts by weight of PA12, 41 parts by weight of PA66 / 6 copolymer, 16 parts by weight of dynamic cross-linking toughening agent, 0.5 parts by weight of antioxidant 445 and 0.5 parts by weight of E wax were mixed evenly, put into a twin-screw extruder for melt blending and extrusion granulation to obtain a high-flowability, low-temperature-resistant, super-tough PA composite material.
[0071] Comparative Example 1
[0072] Based on Example 1, the addition of the compound containing a dynamic covalent bond is eliminated.
[0073] Comparative Example 2
[0074] Based on Example 1, the addition of weakly alkaline metal hydroxide is eliminated.
[0075] Comparative Example 3
[0076] On the basis of Example 1, the compounding scheme of PA with different structures was cancelled, and 42 parts of PA6 and 41 parts of PA66 were changed to 83 parts of PA66.
[0077] Comparative Example 4
[0078] The required PA resin was dried in advance, and then 42 parts of PA6, 41 parts of PA66, 16 parts of toughening agent, 0.5 parts of antioxidant (1098 and s9228 ratio 3:2), and 0.5 parts of OP wax were added into a mixer and mixed evenly, and then added into a twin-screw extruder for melt blending and extrusion granulation to obtain a PA composite material. The toughening agent was commercially available EPDM-g-MAH.
[0079] Comparative Example 5
[0080] On the basis of Comparative Example 4, the toughening agent was changed to commercially available POE-g-MAH.
[0081] Material testing methods
[0082] Tensile properties test: Tested in accordance with standard ISO 527-2;
[0083] Normal temperature impact performance: Test the simply supported beam notched impact strength according to standard ISO 179-1;
[0084] Low temperature impact resistance: After conditioning the notched impact specimen, place it in a -30°C low temperature freezer for 4 hours. After freezing, take it out quickly and test the simply supported beam notched impact strength according to standard ISO 179-1.
[0085] Melt flow properties: The melt index of the composite particles was tested according to standard ISO 1133-1, and the test conditions were 275°C / 5kg.
[0086] All test specimens were prepared by injection molding. The test results are shown in Table 1.
[0087] Table 1 Performance test results of nylon composite materials prepared in Examples and Comparative Examples
[0088]
[0089] Table 1 shows the performance test results of the PA composite materials prepared in various embodiments and comparative examples. From the comparison of the test results of embodiments 1-6 and comparative examples 1-5 in the table, it can be seen that the dynamic crosslinking toughening agent prepared in the present invention plays an important role in the tensile strength, impact strength and fluidity of the PA composite material.
[0090] From the comparison of the test results of Examples 1-3 and Comparative Examples 4-5, it can be seen that the dynamic crosslinking toughening agent of the present invention has obvious advantages in terms of tensile strength, impact and fluidity compared with the toughening agents of the same type on the market after modification of PA composite materials. At the same time, it can be seen that the POE toughening agent has a better impact performance at room temperature, while the EPDM toughening agent has a better impact performance at low temperature. In addition, the reason why the impact performance of Example 2 is lower than that of Examples 1 and 3 is mainly due to the small amount of maleic anhydride, initiator and dynamic crosslinking compound added in the toughening agent system.
[0091] From the comparison of the test results of Example 1 and Comparative Examples 1-2, it can be seen that by introducing dynamic covalent bonds and metal coordination ions into the elastomer toughening agent, the tensile strength, impact resistance, low temperature resistance and fluidity of the PA composite material can be improved to a certain extent. This may be because this method not only reduces the degree of chemical permanent crosslinking in the elastomer toughening agent, but also improves the compatibility between the elastomer toughening agent and PA.
[0092] From the comparison of the test results of Examples 1, 4-6 and Comparative Example 3, it can be seen that the present invention significantly improves the toughness of the composite material by compounding PA resins of different structures as the matrix. This may be because the blending of PA resins of different structures can mutually restrict the crystallization behavior of the molecular chains, which is conducive to forming a complex interpenetrating network structure with the toughening agent, and has a certain improvement on the toughness and fluidity of the composite material. In addition, the effect is most significant when the addition amount of PA resins of different structures is close to 1:1.
[0093] In view of the above results, the high-fluidity, low-temperature-resistant and ultra-tough PA composite material of the present invention is of great significance for expanding the application of PA materials in high-speed railways, automobiles, sporting goods and cold storage equipment parts.
[0094] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.
Claims
1. A high-fluidity, low-temperature-resistant, ultra-tough nylon composite material, characterized in that: It includes the following components, by weight: 23-64 parts of monomer homopolymer nylon; 28-54 parts of multi-molecular monomer copolymer nylon; 7-22 parts of dynamic cross-linking toughening agent; 0.2-0.8 parts of antioxidant; 0.2-0.8 parts of lubricant; The dynamic cross-linking toughening agent comprises ethylene octene copolymer, ethylene propylene diene monomer rubber, maleic anhydride powder, a compound containing a dynamic covalent bond, a lubricant and an antioxidant, and is formed by treating an initiator and a weakly alkaline metal hydroxide. The method for preparing the dynamic cross-linking toughening agent comprises the following steps: a) uniformly mixing ethylene octene copolymer, EPDM rubber, maleic anhydride powder, a compound containing a dynamic covalent bond, a lubricant and an antioxidant to obtain a primary mixture; b) feeding the primary mixture into a twin-screw extruder, feeding a saturated solution of an initiator in ethanol at room temperature through a liquid metering pump at a first side feeding port, and feeding a weakly alkaline metal hydroxide through a second side feeding port; c) extruding and granulating at a temperature of 70-200° C. to obtain the dynamic crosslinking toughening agent.
2. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: The monomer homopolymer nylon is at least one of PA6, PA11 or PA12, and the multi-molecular monomer copolymer nylon is at least one of PA66, PA66 / 6 copolymer, PA56, PA46, PA610, PA612, PA1010, PA1012 or PA1212.
3. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: The components of the dynamic cross-linking toughening agent include 35-64 parts of ethylene octene copolymer (POE), 35-61 parts of ethylene propylene diene monomer (EPDM), 0.5-2.9 parts of maleic anhydride powder, 0.1-0.3 parts of a compound containing a dynamic covalent bond, 0.2-0.4 parts of a lubricant and 0.2-0.4 parts of an antioxidant.
4. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: The initiator is one of diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxide hexane (DBPH), dibenzoyl peroxide or diisopropylbenzene di-tert-butylperoxide, and the weakly alkaline metal hydroxide is at least one of aluminum hydroxide, copper hydroxide, zinc hydroxide, magnesium hydroxide, nickel hydroxide or manganese hydroxide.
5. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: The dynamic covalent bond-containing compound is prepared by chemical reaction of at least one of 1-mercaptoglycerol and α-allyl glyceryl ether and phenyl-1,4-diboric acid, and the reaction product is at least one of double-terminated vinyl borate, double-terminated mercapto borate or mercapto vinyl borate.
6. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BHT, antioxidant 1010, antioxidant 1098, antioxidant 245, antioxidant 1076, antioxidant AO-30, antioxidant 3391, antioxidant 445, antioxidant H3336, antioxidant PolyAd HS-02, antioxidant s9228, antioxidant 168, antioxidant 626 or antioxidant PEPQ.
7. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: The lubricant is at least one of calcium stearate, OP wax, E wax, rice bran wax, silicone powder, ethylene bis stearamide or pentaerythritol stearate.
8. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: When the dynamic cross-linking toughening agent is prepared, the feeding amount of the main feed of the screw extruder is 99-100 parts by weight, the injection amount of the liquid metering pump at the first side feeding port is 0.2-0.6 parts, and the feeding amount of the metering scale at the second side feeding port is 0.4-0.8 parts.
9. The high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to claim 1, characterized in that: When preparing the dynamic cross-linking toughening agent, the temperatures of zones 1 to 12 of the extruder are set to 70±10°C, 170±10°C, 180±10°C, 190±10°C, 200±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, 190±10°C, and the head temperature is 200±10°C.
10. A method for preparing a high-fluidity, low-temperature-resistant, ultra-tough nylon composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: a) drying the nylon resin; b) putting the monomer homopolymer nylon, multi-molecular monomer copolymer nylon, dynamic cross-linking toughening agent, antioxidant and lubricant into a mixer according to the required weight proportions and mixing them evenly; c) adding the mixture into a twin-screw extruder for melt blending, and extruding and granulating to obtain the high-fluidity, low-temperature-resistant and ultra-tough nylon composite material.
Citation Information
Patent Citations
A brominated flame-retardant polyamide composite material and its preparation method and application
CN116102881B
Cited By
High-filling high-heat-resistance flame-retardant nylon material for electric vehicle and preparation method thereof
CN120623766A